Enhancing Machinability in the Heat Treatment of Inconel 718: A Comprehensive Review - Devakant Baviskar; Prasanna Raut (International Journal of Energy and Thermal Applications, 2024)
The increasing need for materials with high strength and heat resistance, particularly in aerospace applications, creates machining issues. These materials are generally difficult to machine because to their strong wear resistance, abrasion resistance, and low heat conductivity. This produces strong cutting forces and temperatures, resulting in a limited tool life. variances in the microstructures of various materials can induce variations in machinability due to variances in chemical composition, casting, forging processes, and heat treatments. Different heat treatments are applied to the alloy Inconel 718, which has an austenitic matrix with a unique microstructure containing the γ matrix, γ' precipitates, γ” precipitates, δ precipitates and carbides. Using annealing processes at various heating temperatures and cooling rates can improve machinability and tool life. Annealing heats the metal above its critical temperature and then cools it slowly over time in a medium. The adhesion and hardness properties of Inconel 718 contribute to short tool life. Careful evaluation of elemental distribution, grain morphology, and texture using analysis methods like TEM, SEM, EDS, and OM provides understanding of the built material's properties. In summary, heat treatments like annealing can help overcome the machining challenges of high-strength, heat-resistant alloys like Inconel 718 by optimizing their microstructure.
Keywords: Heat treatment; Inconel 718; Tool wear; material's properties; microstructure